Marketplace governance in the context of empowering MSMEs inside the realm of online shopping - Eny Haryati; Amirul Mustofa; Litafira Syahadiyanti; S. Suyanto; Sri Juni Woro Astuti (Journal of Community Service and Empowerment, 2023)
The development of online markets in Indonesia that sell imported goods at low prices has caused many MSMEs to go collapse. To accelerate the Sustainable Development Goals, especially achieving the goal of "a country with no poverty, no hunger, creating decent jobs and economic growth as well as a healthy and prosperous country," MSMEs need to be protected from these problems. This study aims to analyze the prospects for the development of online shopping and its impact on MSMEs and propose improvements to marketplace governance. Method research includes interviews, secondary data studies, literature reviews, and meta-analyses. Research results show that online shopping is a need for future society; the marketplace is increasing in terms of numbers, consumers, and transaction value. The number of MSMEs experiencing collapse has increased due to the inability to compete with marketplace players. It is necessary to improve marketplace governance through regulations to protect MSMEs. Current laws only protect consumers, not yet protect MSMEs. Through marketplace governance, it can empower MSMEs to overcome and prevent poverty and hunger, create decent jobs and economic growth, have a healthy and prosperous life, and accelerate the achievement of the SDGs.